PURCHASING DECISION ON MUSLIM FASHION IN TERMS OF BRAND IMAGE, BRAND AWARENESS, PRICE, AND CELEBRITY ENDORSEMENTS - Sarah, Siti (Universitas Muhammadiyah Kalimantan Timur, 2024)
Concerning clothing and fashion, both the Qur'an and hadith emphasize maintaining modesty, this is reflected in many common elements of Muslim clothing even with diverse interpretations of 'modesty' among Muslims around the world. Muslim clothing fashion trends increasingly look vibrant and easy to use. Not only used during the Eid feast but also used for daily activities Indonesia occupies the third position in global modest fashion consumption of Muslim fashion in Indonesia. Gallery Maliqa which is located at Bandung is a local brand that complements Indonesian Muslim women with various types of clothing that always follow the trend, with its flagship product is the scarf. The purpose of this study is to determine the effect of Brand Image, Brand Awareness, Price, Celebrity Endorsement on purchasing decisions at Small Medium Enterprise Gallery Maliqa. Quantitative research method with descriptive approach and verification using multiple linear regression. The number of respondents is 100 Muslim women with purposive sampling technique. The results showed that brand image did not affect purchasing decisions, while brand awareness, price, and celebrity endorsements affected purchasing decisions for Muslim Maliqa products.